Overview of the Occurrence of Green Tobacco Sickness (GTS) in Tobacco Farming Areas: A Literature Review - Kurniyawan, Enggal Hadi (Journal of Local Therapy, 2023)
One of the occupational health risks of tobacco farmers is Green Tobacco Sickness (GTS). The large number of Green Tobacco Sickness incidents nationally and internationally experienced by green tobacco farmers has led to a great deal of research being conducted to determine the process of occurrence of the disease, the impact on health and other fields, the prevention, and management of this disease. The method used in this literature review is to re-expose published information and then return briefly without reducing the essence of the topic of discussion. The journal used in making literature reviews was obtained from 3 database source, namely Google Scholar, Pubmed, and Science Direct published between 2018-2021. The aim of the study was to describe the incidence of Green Tobacco Sickness in the farmers in the green tobacco farming area. The conclusion of this study is based on some research, it is stated that tobacco farmers already understand about GTS and the symptoms that can arise due to GTS. However, several other studies have shown that the educational level of tobacco farmers is included in the low category where this can affect workers to protect or prevent diseases caused by the work they do. Based on these results, it is hoped that there will be a role for nurses who can support the reduction of Green Tobacco Sickness (GTS) cases such as counseling to green tobacco farmers about the dangers of GTS and prevention efforts such as using good and correct PPE.